A cheap and efficient system for Spongia anclotea farming in the Bahamas - Motta, Gregorio; Auriemma, Rocco; Brooks, Annabelle; Novak, Massimiliano; Pesle, Elena; Terlizzi, Antonio; Avian, Massimo (Frontiers in Marine Science, 2025)
Sponges are now requested for their commercial, industrial and pharmaceutical importance. This led to an increase in demand in the global markets with uncontrolled and excessive harvesting pressure that, together with diseases outbreaks, put wild populations at risk, with several habitats completely looted. Aquaculture of sponge fragments poses an alternative to wild collection since fragment regeneration is easy, cheap and efficient. We chose as subject of our study Spongia anclotea, common to the tropical Western Atlantic, due to its high request on the market for cosmetics, body care and pharmaceutical applications. We set a low-cost sponge farm made of cheap materials, thus affordable for local communities, which did not require significant maintenance. The growth and survival rate of 384 out of 2304 randomly chosen sponges have been investigated over a 4-year period. At the end of the study, sponges increased by an average rate of 380% ± 275% of their initial volume (with a maximum of 1480%) and 87.5% of sponges survived (death and detach during the whole period were considered as mortality). Farmed sponges from our structure resulted characterized by superior quality and shape compared to collected wild individuals from the area and, after six years of cultivation (4 years of the present study + 2 years of forecasted growth based on our findings), this improved quality could yield higher profits (618 USD vs. 547 USD, respectively, for a standard stock size). This experimental setup can be considered a good alternative to sponge harvesting and a good economic opportunity for developing countries.